EKOENZIMM FOR AGRICULTURAL WASTE TREATMENT IN SELODUWUR HAMLET, BATUR VILLAGE, GETASAN DISTRICT: - - Susilorini, Susilorini; Dian Indrayani, Ulfah; Utami, Kamilia; Syafii, Achmad (LPPM Univ. Ibn Khaldun Bogor, 2022)
Organic farming is one of the proponents of food resistance, economic resilience and human health especially during the COVID 19 pandemic. The sustainability of organic farming must be supported by the availability of fertilizer, pesticides and sufficient financial capital. Ecoenzym is one of the easy and inexpensive agricultural waste fermentation products. Ecoenzyme can be one of the solutions to increase the availability of fertilizer, pesticides and can be used to reduce the economic burden due to financial spending on soap, shampoo and household hygiene. In addition, ecoenzymes are also beneficial in restoring fertility and repairing the quality of soil damaged by conventional agriculture using chemical fertilizers and pesticides. Batur Village is one of the villages with an organic farming community that is affiliated in the Minang Bangkit Merbabu farming group. Currently, the organic fertilizer used is the fertilizer and compost that comes from agricultural waste only. Its availability is highly dependent on the limited number of livestock, and not all farmers have livestock. Ecoenzyme training is one of the activities that is expected to be a solution for farmers to jointly produce fertilizer and pesticides, thus increasing the economic level of agricultural waste that is processed into ecoenzymes.